Identification Of Risk Factors Of Bone Metastasis Among Iraqi Breast Cancer Women - Marwa Kahtan Ali; Ahmed Mubarak (International Journal of Health and Medicine, 2024)
Background: The most common site of metastases in people with breast cancer is bone metastasis. Patients with advanced phases of cancer are associated with an increased prevalence of several types of metastases, one of which is bone metastasis. Object: Assessment of the risk factors for bone metastases in patients with breast cancer. Patients and Methods: This is a retrospective study of 316 patients with breast cancer who either had bone metastases at the time of diagnosis or developed it later on. The study was carried out between January 2013 and April 2018. Three hundred and sixteen patients were assigned into two groups. In the case group, 100 patients with breast cancer had been diagnosed with bone metastasis by CT, MRI, bone scan, and PET scan; in the control group, there were 216 cases in are control group with breast cancer metastasis to sites other than bone. The questionnaire was created to record all factors (with the exception of demographic information), such as age, histopathological reading for invasive lobular carcinoma, invasive ductal carcinoma, or another type of cancer, ER status, PR status, Her2neu status, lymph node status and stage, and menopausal status. Results: The majority were 45 years of age or younger, and 96.5% of them had invasive ductal carcinoma in terms of hormonal status. Positive ER and PR status is found in 67.7% and 67.1% of the cases, respectively; 40.5% of the cases had amplified Her2neu receptors, 78.5% of the cases had positive lymph nodes, and 41.9% of the cases had (N1) stage. The highest proportion of bone metastasis was associated with negative ER and PR receptors (46.2% and 49%, respectively), while no significant statistical association (P= 0.65). Conclusion: negative ER, PR status, and Her2neu receptors not amplified, lymph node involvement, age 45 and less, infiltrating lobular carcinoma (ILC) histological type, and menopausal state are significant risk factors for bone metastasis in breast cancer.